Effect of acidosis on the mechanism (s) of insulin-induced vasorelaxation in normal Wistar-Kyoto (WKY) rat aorta - Subramaniam, G.; Achike, F.I.; Mustafa, Mohd Rais (Elsevier, 2009)
The effect of acidosis on insulin-induced relaxation was studied in thoracic aortic rings (from Wistar–Kyoto (WKY) rats) with (+ED) or without (−ED) endothelium. The rings were mounted in normal (pH 7.4) or acidotic (pH 7.2) Krebs solution for isometric tension recording. Phenylephrine (PE, 3.0 µM)-contracted tissues were exposed to insulin in the presence or absence of various inhibitors. Insulin exerted similar concentrationdependent relaxation of +ED tissues in normal and acidotic pH. Endothelium denudation, signiﬁcantly (pb 0.05) reduced insulin effect in normal, but not acidotic pH. Under normal pH, treatment with L-NAME or methylene blue signiﬁcantly (pb 0.05) reduced insulin responses in the +ED (but not the −ED) tissues. The insulin effect was also signiﬁcantly (pb 0.05) inhibited by tetraethylammonium (TEA; BKCa blocker), 4-Aminopyridine (4-AP; KV channel blocker), combined treatments (L-NAME+4-AP+TEA, in +ED tissues) or (4-AP+TEA, in −ED tissues). In either +ED or −ED tissues, indomethacin (cyclo-oxygenase inhibitor), glibenclamide (KATP channel blocker), barium chloride (Kir channel blocker) or Ouabain (a Na+ /K+ -ATPase inhibitor) had no effect. Except for methylene blue (effect on +ED tissues), none of the drug treatments inhibited insulin vasodilator effect in acidosis (+ED or −ED tissues). These data indicate that insulin exerts an endothelium-dependent and - independent vasodilatation in rat aorta which in normal pH is mediated via BKCa and Kv channels, including the EDNO-cGMP cascade. Acidosis abolishes the endothelium-dependent relaxation mechanism unraveling a novel mechanism that is as efﬁcacious and is cGMP-, but not EDNO-, BKCa- or Kv-mediated.